Are we on path to eliminate cervical cancer? An analysis of National Cancer Registry Data from 2005 to 2019 - Malawige Amila Suranga; Janaki Vidanapathirana; Sashiprabha Nawaratne; Thanuja A. Wickramatunga (College of Community Physicians of Sri Lanka, 2022)
Introduction: Cervical cancer is the fourth most common cancer affecting women worldwide. The primary cause for cervical cancer is the persistent or chronic infection with one or more of high-risk oncogenic types of human papilloma virus (HPV). The risk factors for cervical cancer are classified as co-factors favouring acquisition of HPV infection and its persistence. Most cervical cancers can be prevented by risk factor reduction, early detection and treatment at precancerous stage.   Objectives: To analyse the trends of incidence rates, age at diagnosis and histological types of cervical cancer in Sri Lanka from 2005 to 2019   Methods: Data of the National Cancer Registry, Sri Lanka (NCR-SL) of the National Cancer Control Programme (NCCP), Ministry of Health, Sri Lanka were used to calculate the incidence trends from 2005 to 2019 by age at diagnosis and histological type. Joinpoint regression analysis was performed to obtain the average annual percentage change(AAPC).   Results: The crude incidence rate ( CR) of the cervical cancer in Sri Lanka showed a significant increasing trend with an AAPC of 1.7% (95% CI: 0.5, 2.9). The age at diagnosis for the majority was between 45-64 years. A significant increasing trend of the age specific incidence was observed in the 65-74-year age group with the AAPC being 1 .4% (95% CI: 0.0, 2.8). The Age standardized rate (ASR) showed a declining trend which was not statistically significant. Among the histology types, the majority was squamous cell carcinomas but over the study period it showed a declining trend and adenocarcinomas showed an increasing trend. Both the trends were statistically significant. Other histology types showed an insignificant increasing trend.   Conclusions & Recommendations: Sri Lanka shows a significant increasing trend in CR and a declining nonsignificant trend in ASR in cervical cancer during 2005-2019. Further, the peak age group of diagnosis was 45-64 years, with an increasing trend in incidence in the 65-74-year age group. Squamous cell type cancer showed a significant declining trend in contrast to a significant increasing trend for adenocarcinoma type. Preventive strategies for cervical cancer should be further strengthen with special emphasis on HPV vaccination, screening and increasing awareness among public.